ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DAN PENGUPAHAN (Studi Kasus Pada PT. Pratama Abadi Industri JX) - Mursidah, Ajeng Aulia; Nugroho, Gatot Wahyu; Eriswanto, Elan (Universitas Nusantara PGRI Kediri, 2020)
The Payroll and Wage System of PT. Pratama Abadi Industri Sukabumi (JX) in its application is already good because in this company already uses a computerized system. Some functions and parts are carried out by one different department. Documents used in the remuneration and remuneration system still have discrepancies because in this company already using a computerized system, the procedure in the payroll and remuneration system is done well, it can be seen from several payroll and wage procedures that are appropriate and regular. records that are used in the remuneration and remuneration system are still incompatible, internal controls related to the payroll and remuneration processes are good, it can be seen that some activities, especially in remuneration and remuneration are carried out by several different parts and responsibilities.